Synthesis and characterisation of maltosides and lactosides based on alcohol mixtures obtained from palm oil and palm kernel oil / Nurul Fadhilah binti Kamalul Aripin - Kamalul Aripin, Nurul Fadhilah (2009)
The headgroup of these glycolipids, which consist of a dissacharide i.e. maltose and lactose, provide good hydrophilicity. These glycolipids are comparable to alkyl polyglucosides (APGs), a common non-ionic surfactant used for detergents, particularly in the cosmeceutical industry. APGs are limited to high lipophilicity due to their low degree of polymerisation (~1.5) and their chemical diverse compositions make them unsuitable for bio-related applications. Technical grade glycolipids based on alcohol mixtures from reduced palm oil and palm kernel oil were investigated to explore their application as surfactants. The technical grade glycolipids were synthesized using a method that produces “clean” anomeric mixtures with no significant non-glycoside contamination, making them suitable for biotechnology application. The investigations involved thermotropic and lyotropic behaviour of the glycolipids mixtures. Two major effects were investigated separately; stereochemical effect and chain effect. Studies on stereochemical effects were performed on dodecyl (C12) model compounds, comprising various α/β ratios based on different synthetic approaches. The chain effect study was devided in two categories; chain length and chain inhomogeneity. The clearing transition temperatures of palm oil and palm kernel oil maltosides are influenced by the unsaturated compounds while the lactosides‟ are more complicated. High unsaturation in palm oil maltosides showed a cubic phase but the palm oil and palm kernel oil lactosides have no significant difference in their lyotropic phase behaviour